2011
DOI: 10.3989/gya.113610
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial activity in the seeds of <i>Origanum vulgare</i> L. subsp. <i>gracile</i> (C. Koch) Ietswaart and <i>Origanum acutidens</i> (Hand.-Mazz.) Ietswaart from Turkey

Abstract: RESUMENEn el presente estudio se han determinado algunos compuestos biológicos (ácidos grasos, vitaminas, esteroles y flavonoides), la capacidad de secuestrar radicales libres y la actividad antimicrobiana de dos especies de orégano, Origanum vulgare L. subsp. gracile (C. Koch) Ietswaart y Origanum acutidens (Hand.-Mazz.) Ietswaart. El ácido linolénico (C 18:3 ) mostró ser el principal ácido graso en ambas especies, seguido por los ácidos palmítico (C 16:0 ), esteárico (C 18:0 ), oleico (C 18:1 n9), linoleico … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…After 30 minutes of darkness and room temperature, samples were read at 517 nm in a spectrophotometer. DPPH• Radical Sweep Percentage % = [(A0 -A1)/A0] x 100 A0: Control absorbance, A1: Sample absorbance (Kürşat et al, 2011).…”
Section: Dpph Radical Reduction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 30 minutes of darkness and room temperature, samples were read at 517 nm in a spectrophotometer. DPPH• Radical Sweep Percentage % = [(A0 -A1)/A0] x 100 A0: Control absorbance, A1: Sample absorbance (Kürşat et al, 2011).…”
Section: Dpph Radical Reduction Methodsmentioning
confidence: 99%
“…It was discovered that it was 220 nm for retinol acetate. The Class Vp 6.1 program was used, and the findings were expressed in terms of g/g (Bahşi, 2008;Kürşat et al, 2011).…”
Section: Vitamin and Sterol Analysismentioning
confidence: 99%
“…The essential oils from wild and cultured form of Salvia pisidica showed cytotoxicity on H1299 cells24. In other studies, it has been reported that O. acutidens essential oil showed antimicrobial activity against different bacterial species(20,21).By culturing endemic species in different physical conditions, we can make them show similarities with the wild form. It has been reported in many studies that essential oils and their components obtained from plants had anticancer effects by creating cytotoxic effects on cancer cells.…”
mentioning
confidence: 92%
“…Among traditional medical uses of the Origanum species, the treatment of abdominal pain, toothache, headache, diabetes, infections of the urinary tract, gastrointestinal and pulmonary diseases was reported [ 12 , 13 , 14 ]. Previous studies have shown antibacterial, antifungal, anticancer, antidiabetic, antinociceptive, insecticidal and phytotoxic activities for some Origanum species [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Interestingly, their essential oils (EOs) also showed ferric reducing and antioxidant properties [ 22 ].…”
Section: Introductionmentioning
confidence: 99%